Stillbirth in twin pregnancies in Stockholm County 2000–2021—A descriptive study - Matilda Varli Hjärne; Cecilia Pegelow Halvorsen; Hanna Åmark (PLoS ONE, 2025)
Introduction The incidence of stillbirth is higher in twin pregnancies compared with singleton pregnancies. Known risk factors for stillbirth in twin pregnancies include selective fetal growth restriction, twin-to-twin transfusion syndrome (TTTS) and preeclampsia. However, the full range risk factors and causes of stillbirth in twin pregnancies remain incompletely explored. Aim The aim was to describe the incidence of stillbirth in twin pregnancies, identify associated risk factors, explore the causes of stillbirth, and examine pregnancy characteristics. The comparisons were made according to chorionicity and between twin and singleton stillbirths. Materials and methods This descriptive register-based cohort study included 1978 singleton and 193 twin stillbirths in Stockholm County, from 2000 until 2021, using data from Stockholm Stillbirth Group and Swedish Pregnancy Register. Twin stillbirths with different chorionicity were compared with each other and with singleton stillbirths, respectively. Results Twin pregnancies had a higher incidence of stillbirth compared with singleton pregnancies. Between 2000 and 2021, the incidence of singleton stillbirth decreased from 4.7 to 3.4 and the incidence of twin stillbirth decreased from 14.2 to 7.2 per 1000 births, respectively. Twin stillbirth occurred at an earlier gestational age, and fetuses in twin stillbirths had lower birth weight compared with singleton stillbirths. In monochorionic twin pregnancies, stillbirth was strongly associated with TTTS, identified as the main cause of stillbirth. The causes of stillbirth among dichorionic pregnancies were similar with those of preterm singleton stillbirth, with placental insufficiency and fetal growth restriction, as the most common causes. Conclusions The risk of stillbirth in twin pregnancies was more than twice as high as in singleton pregnancies, although both incidences decreased over time. Stillbirth among monochorionic twins was especially associated with the unique risk factor TTTS. Causes of stillbirth among dichorionic twin pregnancies were similar with those of preterm singleton stillbirth.